Application of the acoustic emission method in fatigue cracking and fracture toughness estimation for steel - S. PILECKI; J. SIEDLACZEK (Archives of Acoustics)
The present paper consists of the confirmation of previous works where the great variety of the acoustic emission (AE) characteristics of different metals have been found. Based on the experiments conducted for the St90PA steel, possibilities of the fatigue cracks initiation detection by use of the AE method are discussed herein. Relations between the fatigue crack length and AE count rate or count sum have been determined and the possibilities of the application of AE in fracture toughness estimation as well as in critical stress intensity factor K1c calculations have been presented. It has been stated that creation of the fatigue cracks in steel can be detected much earlier by use of the AE method than it was possible by use of the classical optical method. AE method also makes the estimation of the propagating crack length easier as well as it can make the estimation of the fracture toughness more accurate.